2011
DOI: 10.21161/mjm.02611
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological evaluation of some sachet water on sales in Owerri metropolis, Imo State, Nigeria

Abstract: Aims: Continuous increase in the sale and indiscriminate consumption of packaged drinking waters in Nigeria is of public health significance. In order to safe guard public health, it is essential that the available packaged water is of the highest quality. This study was carried out to evaluate the bacteriological quality of packaged water on sale in Owerri metropolis, Imo State of Nigeria. Methodology and Results: From 30 registered sachet water factories, 8 samples each was purchased randomly fifteen of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Another study by Ezugwune et al [34] analyzed the prevalence of bacteria in packaged sachets water sold in Nnewi, South East, Nigeria and reported that percentages of the different organism isolated from drinking water, were E. coli (36%), Streptococcus faecalis (19.4%), Klebsiella pneumoniae (19.4%) and Staphyloccocus aureus (25%). This is in agreement with the findings of a study which analyzed a total of 50 drinking water samples comprising; 20 well water, 15 sachet water, 10 borehole water and 5 river water in Sokoto, Northwest Nigeria, the distribution of the bacteria isolated and identified from the study indicated that Escherichia coli had the highest total prevalence of (40.31%) occurring in all the water samples, [36]. In a separate study conducted in Maiduguri, North eastern Nigeria, Muazu reported that 55% of the brands of packaged sachet water analyzed had fecal coliforms, 25% had Pseudomonas aeruginosa, 15% had Salmonella sp.…”
Section: Discussionsupporting
confidence: 90%
“…Another study by Ezugwune et al [34] analyzed the prevalence of bacteria in packaged sachets water sold in Nnewi, South East, Nigeria and reported that percentages of the different organism isolated from drinking water, were E. coli (36%), Streptococcus faecalis (19.4%), Klebsiella pneumoniae (19.4%) and Staphyloccocus aureus (25%). This is in agreement with the findings of a study which analyzed a total of 50 drinking water samples comprising; 20 well water, 15 sachet water, 10 borehole water and 5 river water in Sokoto, Northwest Nigeria, the distribution of the bacteria isolated and identified from the study indicated that Escherichia coli had the highest total prevalence of (40.31%) occurring in all the water samples, [36]. In a separate study conducted in Maiduguri, North eastern Nigeria, Muazu reported that 55% of the brands of packaged sachet water analyzed had fecal coliforms, 25% had Pseudomonas aeruginosa, 15% had Salmonella sp.…”
Section: Discussionsupporting
confidence: 90%
“…These are small nylon sachets containing 0.5L of water which are electrically heated and sealed at both ends (Adegoke et al, 2012). The sale and consumption of packaged water continue to grow astronomically and rapidly in most countries of the world (Mgbakor et al, 2011;Oyedeji et al, 2010;Gangil et al, 2013).…”
Section: Satchet Watermentioning
confidence: 99%
“…Production, sales and consumption of packaged water is growing rapidly in most countries of the world especially in developing countries (Oyedeji et al, 2010;Mgbakor et al, 2011;Gangil et al, 2013). Many scientists all over the world have carried out researches on the microbial analysis of commercially vended packaged water using different laboratory techniques and reporting varying percentages of microbial isolation (Warburton et al, 1992;Bharath et al, 2003;Oladapo et al, 2009;Prasanna and Reddy, 2009;Kuitcha et al, 2010;Oludairo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[5] The sale and consumption of packaged drinking water continues to grow rapidly in most of the developing countries of the world. [6] In order to safeguard public health it is essential that the available packaged water is of the highest quality. [7] The continuous proliferation of these packaged drinking water and their indiscriminate consumption are of concern to public health.…”
Section: Introductionmentioning
confidence: 99%